2008
DOI: 10.3858/emm.2008.40.4.461
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pro-inflammatory responses by lipoxygenases via intracellular reactive oxygen species in vitro and in vivo

Abstract: Reactive oxygen species (ROS) performs a pivotal function as a signaling mediator in receptor-mediated signaling. However, the sources of ROS in this signaling have yet to be determined, but may include lipoxygenases (LOXs) and NADPH oxidase. The stimulation of lymphoid cells with TNF-α, IL-1β, and LPS resulted in significant ROS production and NF-κB activation. Intriguingly, these responses were markedly abolished via treatment with the LOXs inhibitor nordihydroguaiaretic acid (NDGA). We further examined in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 64 publications
1
48
0
Order By: Relevance
“…Moreover, extracellular signalregulated kinase 1/2 (ERK1/2), a protein kinase of the P38/Mitogenactivated protein kinase (MAPK) family, can also mediate the inflammation process [21]. Under normal physiological conditions, phosphorylated ERK1/2 activates cytosolic phospholipases A2 (cPLA2) and leads to the formation of COX-2, an enzyme that produces prostaglandins (PGs) [22]. In lipopolysaccharide-activated macrophages, 1 μM garcinol inhibited the production of COX-2 and PGs.…”
Section: In Vitro Studies On Anti-inflammatory Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, extracellular signalregulated kinase 1/2 (ERK1/2), a protein kinase of the P38/Mitogenactivated protein kinase (MAPK) family, can also mediate the inflammation process [21]. Under normal physiological conditions, phosphorylated ERK1/2 activates cytosolic phospholipases A2 (cPLA2) and leads to the formation of COX-2, an enzyme that produces prostaglandins (PGs) [22]. In lipopolysaccharide-activated macrophages, 1 μM garcinol inhibited the production of COX-2 and PGs.…”
Section: In Vitro Studies On Anti-inflammatory Effectsmentioning
confidence: 99%
“…A physical analysis of garcinol identified a melting point of 122°C and optical rotation of [α] 22 D − 143°(1% chloroform). The molecular formula, C38H50O6, was suggested to have structural similarities to xanthochymol (molecular mass: 602.82 and [α] 22 D +141°(1% chloroform), a prenylated chalconoid previously discovered from Garcinia xanthochymus [4]. However, based on its optical rotation sign, garcinol may be more closely associated with cambogin (molecular mass: 602.27 and [α] 22 D − 132.9°(1% chloroform) [8,9], an isoprenylated benzophenone derivative isolated from G. cambogia and characterized by Venkatsuamy et al [4,5].…”
Section: Chemical Structure and Properties Of Garcinolmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these highly reactive molecules regulate many important cellular events, including transcriptional factor activation (Lo and Cruz, 1995;Sulciner et al, 1996;Bubici et al, 2006), cellular proliferation (Irani et al, 1997), and apoptosis (O'Donnell et al, 1995) in a variety of non-phagocytic cells, the generation of ROS is not yet well characterized. Recently, potential roles of the mitogenic oxidase Nox family NADPH oxidases (Lambeth et al, 2000;Petry et al, 2010) and/or 5-lipoxygenase (5-LO), which catalyzes the production of leukotrienes and ROS from arachidonic acid (Harrison and Murphy, 1995;Catalano et al, 2005;Kim et al, 2008), have been demonstrated in the generation of ROS following receptor ligation in various cell types.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the immunological pathogenesis of asthma, Th2 cytokines, such as IL-4, IL-5, IL-9, and IL-13, are considered to be key mediators of the development of asthma phenotypes, such as airway inflammation and AHR (Mosmann et al, 1986;Kim et al, 2008). IL-13 is now believed to be a central mediator in the development of allergic asthma (Wills-Karp et al, 1998).…”
Section: Discussionmentioning
confidence: 99%